The Influence of Islamophobia on Violence Against Muslims in India - Anam, Syaiful; Mar'atun, Chairanil; Hidayat, Alfian (Ulumuna, 2024)
Following the 9/11 attacks, there has been an increase in Islamophobia. The wave of Islamophobia is not only found in European countries but also grows in Asian countries, including India. India has long been the location of a great, developing world civilization. The Hindu-Muslim conflict shaped India's rise to independence. Since the election of Prime Minister Narendra Modi in 2014, India has indicated that it will become a Hindu-centric country that increasingly marginalizes Muslim minorities. The purpose of this study is to examine the effect of Islamophobia on violence against Muslims in India during the reign of Prime Minister Narendra Modi and to understand the form of multidimensional violence and the causes of the development of Islamophobia. This study shows that there is an influence of Islamophobia on the continuity of violence in Indian society, especially involving Hindu and Muslim groups. Islamophobia is also manifested through multidimensional violence, such as direct violence, structural violence, and cultural violence. The presence of Hindutva ideology, the influence of right-wing groups, and Indian media all contribute to the growth of Islamophobia in India.